CRYSTALLOGRAPHIC-MAGNETIC CORRELATIONS IN SINGLE-CRYSTAL HAEMO-ILMENITE: NEW EVIDENCE FOR LAMELLAR MAGNETISM - Robinson P.; McEnroe S.A.; Heidelbach F.; Hirt A.M.; Brown L.L. (My University, 2006)
17 single crystals were identified by electron backscatter diffraction (EBSD) and isolated from coarse massive haemo-ilmenite ore from South Rogaland, Norway. These were studied using the EBSD results, natural remanent magnetization (NRM), and anisotropy ofmagnetic susceptibility (AMS), to gain a better understanding of angular relationships between crystallographic axes and magnetic properties of haemo-ilmenite in relation to lamellar magnetism. Electron microprobe analyses gave the following average end-member compositions for ilmenite host: 21.1 per cent MgTiO3, 73.7 FeTiO3, 0.5 MnTiO3, 4.3 Fe2O3, 0.2 Cr2O3 and 0.3 V2O3; and for the coarsest (~3 μm) haematite exsolution lamellae: 3.5 MgTiO3, 22.4 FeTiO3, 71.4 Fe2O3, 1.6 Cr2 O3, 1.0 V2O3 and 0.1 Al2 O3, making this sample the most Mg- and Cr-rich haemoilmenite studied in the province, but with similar element fractionations between the coexisting phases. TEM work on similar material suggests the presence of much thinner exsolution down to 1-2 nm. The EBSD, NRM and A MS results from 12 out of 17 crystals indicate a good agreement between the orientation of crystallographic axes, NRM direction and principal axes of the magnetic susceptibility ellipsoid, with the NRM located in the (0001) basal plane [NRM Λ (0001) < 6.5°] and the crystallographic c axis quasi-parallel to the minimum axis of the susceptibility ellipsoid [cΛ k3 < 13.5°]. In addition, in 10 of these 12 crystals, the remanent magnetization vector is parallel or nearly parallel to the positive direction of a crystallographic a axis [NRM. a < 20°], hence parallel to a principal magnetic moment direction in haematite as determined by Besser et al., and not parallel to the spin-canted direction of end-member haematite. This is consistent with a basic property of lamellar magnetism, where the magnetic moment is parallel to the principal moments (sublattice magnetization directions) in haematite. Relationships in three additional crystals with NRM Λ a = 22°-33°, only two with good agreement, can be interpreted as consistent with having a magnetic vector quasi-parallel to the spin-canted direction of haematite. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: ANISOTROPY OF MAGNETIC SUSCEPTIBILITY; ELECTRON BACKSCATTER DIFFRACTION; HAEMATITE; HAEMO-ILMENITE; LAMELLAR MAGNETISM; NATURAL REMANENT MAGNETIZATION